From the Peripheral to the Transboundary: Documenting the Lived Experiences of Students and Parents with Online Math Tutoring Services - Azan, Alaa (Université d'Ottawa / University of Ottawa, 2021)
Tutoring services have experienced exponential increases in enrollment in Canada, with Ontario alone witnessing a 60% increase in enrollment from 1996 to 2000 (see Aurini & Davies, 2004). While Canadian research has documented organizational changes (Aurini & Davies, 2004; Aurini, 2006) and parents’ motives to enroll in tutoring services (Davies, 2004; Gale, 2016), the lived experiences of students with tutoring services are notably absent from the literature to date. In response, the current study investigates the experiences of high school students receiving math tutoring services (n =3) and their parents (n =2). The extent to which their participation in tutoring demonstrates “transboundary learning” (Kim & Jung, 2019b) is also examined in response to claims that tutoring services represent mainly peripheral learning environments as opposed to a core part of students’ learning (Aurini & Davies, 2013). Guided by a poststructuralism theoretical framework, the study employs qualitative methods to respond to three questions: (1) What are the lived experiences of high school students receiving math tutoring from a private tutoring service in Ottawa (Ontario, Canada)? (2) What are parents’ motives for seeking private tutoring services? and (3) How do participants perceive the learning taking place in different environments (e.g., tutoring vs. school)? Data from semi-structured interviews with high school students and their parents are analyzed using thematic analysis and interpreted using a Transboundary Learning framework (Kim & Jung, 2019b). Findings reveal key characteristics of transboundary learning in participants’ math tutoring contexts, suggesting a shift in the relationship between tutoring and schooling from peripheral to transboundary learning, whereby, tutoring is not regarded as peripheral as it has been in the literature to date. These findings are discussed in light of the noteworthy influence of tutoring over students' learning and schooling, and the potential for more inequalities in education.
Keywords: Online tutoring; math tutoring; transboundary learning; students; parents; lived experiences